Polyoxometallate-polyvinyl acetal composite membrane as well as preparation method and application thereof
Through the preparation of polyoxometalate-polyvinyl acetal composite membrane, the problems of complex preparation process and high cost of perfluorosulfonic acid proton exchange membrane were solved, and the solvent resistance and mechanical properties of the proton exchange membrane were improved, making it suitable for use in hydrogen proton exchange membrane fuel cells.
Patent Information
- Application Number
- CN202510631914.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-16
- Publication Date
- 2025-09-12
AI Technical Summary
Existing perfluorosulfonic acid proton exchange membrane fuel cell proton exchange membrane has problems such as complex preparation process, high cost and poor solvent resistance, which limits its large-scale application in hydrogen proton exchange membrane fuel cells.
A polyoxometalate-polyvinyl acetal composite membrane is used. By combining polyvinyl acetal with polyoxometalate molecular clusters, a composite membrane with good compatibility is formed. The hydrophobicity of polyvinyl acetal and the hydrophilicity of polyoxometalate are utilized to form a continuous and efficient ion conduction channel, thereby enhancing solvent resistance and mechanical properties.
The proton exchange membrane has excellent solvent resistance, high ion transfer efficiency, good conductivity, high thermal stability, and strong mechanical properties, which reduces production costs and is suitable for large-scale industrial production and application.
Smart Images

Figure CN120637550A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fuel cells, and in particular to a polyoxometalate-polyvinyl acetal composite membrane and a preparation method and application thereof. Background Art
[0002] A proton exchange membrane fuel cell (PEMFC) is a highly efficient device that converts the chemical energy of hydrogen and oxygen directly into electrical energy. Its low emissions, fast start-up, and high efficiency make it widely used in transportation, stationary power supplies, and portable devices. The proton exchange membrane (PEM) is the core component of a PEMFC, conducting protons and isolating gases. It also collaborates with components such as catalysts, gas diffusion layers, and bipolar plates to complete the electrochemical reaction. Therefore, the development of PEMs is crucial to PEMFCs.
[0003] Perfluorosulfonic acid proton exchange membranes (e.g., Nafion membranes) are a widely used type of proton exchange membrane with advantages such as good chemical stability, high electrical conductivity, and high mechanical strength. However, due to the complex preparation process, high cost, and generation of fluorine-containing waste, fluorinated materials are no longer able to fully meet the growing demand for practical applications. Organic-inorganic composite proton exchange membranes have the advantages of simple preparation process, relatively low production cost, and abundant raw material resources, and have become a research hotspot in recent years. Research shows that the key to developing organic-inorganic composite proton exchange membranes lies in the effective combination of organic polymer components and inorganic components, so as to fully utilize the high mechanical strength, processability, and gas barrier properties of the organic polymer component and the high proton conductivity of the inorganic component (e.g., superacidic nanoparticles).
[0004] Polyvinyl alcohol (PVA) is a hydrophilic, fluorine-free polymer with good processability, film-forming properties, and barrier properties. PVA contains a large number of hydroxyl groups, which can provide supramolecular binding sites for various acidic nanoparticles, achieve strong complexation between polymers and inorganic particles, and thus provide an excellent material development platform for the development of PVA-based composite proton exchange membranes. At the same time, the preparation of PVA does not require a synthetic process such as fluorination, which greatly reduces the preparation cost of the material. However, due to the strong polarity and hydrophilicity of PVA, the composite proton exchange membranes currently prepared with PVA as the polymer matrix generally have the problem of poor water resistance and organic solvent resistance. In the production and testing process of the proton exchange membrane, it is usually necessary to spray the catalyst slurry on the membrane surface. The surface of the PVA-based membrane is easily exposed to the organic solvent in the catalyst slurry (for example, a mixed solvent of alcohols and water) and may cause excessive expansion or defects, which will eventually affect the performance of the proton exchange membrane and seriously limit the large-scale application of PVA-based composite proton exchange membranes.
[0005] Therefore, it is of great significance to develop a proton exchange membrane with excellent solvent resistance, high ion transfer efficiency, good conductivity, high thermal stability, good mechanical properties, low production cost, and green and streamlined manufacturing process. Summary of the Invention
[0006] The purpose of the present invention is to provide a polyoxometalate-polyvinyl acetal composite film and a preparation method and application thereof.
[0007] The technical solution adopted by the present invention is:
[0008] A polyoxometalate-polyvinyl acetal composite film comprises polyvinyl acetal and polyoxometalate molecular clusters. The polyvinyl acetal is prepared by reacting polyvinyl alcohol and a straight-chain aldehyde compound.
[0009] Preferably, the mass ratio of the polyvinyl acetal to the polyoxometalate molecular cluster is 1:0.5-8.
[0010] More preferably, the mass ratio of the polyvinyl acetal to the polyoxometalate molecular cluster is 1:2-4.
[0011] Preferably, the polyoxometalate molecular cluster is a Keggin-type polyoxometalate molecular cluster.
[0012] Preferably, the general structural formula of the Keggin-type polyoxometalate molecular cluster is as follows: n [XM 12 O 40 ] n- ·mH2O, wherein X represents the central atom, X is selected from at least one of P, Si, Co, and Al, Y represents the counter ion, Y is selected from at least one of H, Li, Na, and K, M represents the coordinating atom, M is selected from at least one of Nb, W, and Mo, m represents the number of crystal waters, the number of m depends on the self-bound water and the specific environmental humidity, m is an integer from 0 to 40, and n represents the number of charges carried by the polyanion / the number of counter ions, and n is 3, 4, or 6.
[0013] Further preferably, the Keggin type polyoxometalate molecular cluster is a phosphotungstic acid molecular cluster (X3[PW 12 O 40 ] 3- mH2O), silicotungstic acid molecular clusters (X4[SiW 12 O 40 ] 4- At least one of mH2O.
[0014] More preferably, the Keggin type polyoxometalate molecular cluster is a phosphotungstic acid molecular cluster H3[PW 12 O40 ] 3- mH2O (abbreviated as PW 12 ), silicotungstate molecular cluster H4[SiW 12 O 40 ] 4- ·mH2O (abbreviated as SiW 12 ) at least one of.
[0015] Preferably, the molar ratio of the hydroxyl group in the polyvinyl alcohol to the aldehyde group in the linear aldehyde compound is 1:0.125-0.375.
[0016] Preferably, the number average molecular weight of the polyvinyl alcohol is 30,000 g / mol to 300,000 g / mol.
[0017] Further preferably, the polyvinyl alcohol is at least one of Kuraray (Kuraray Co., Ltd.) PVA124 (number average molecular weight of 67,000 g / mol), Kuraray's PVA224 (number average molecular weight of 85,000 g / mol), and Kuraray's PVA117 (number average molecular weight of 75,000 g / mol).
[0018] Preferably, the straight-chain aldehyde compound is C8~C 12 of straight-chain aldehyde compounds.
[0019] More preferably, the straight-chain aldehyde compound is at least one of octanal and dodecanal.
[0020] Preferably, the polyvinyl acetal is prepared by a preparation method comprising the following steps: dispersing polyvinyl alcohol and a linear aldehyde compound in an organic solvent for reaction, and then purifying and drying the product to obtain the polyvinyl acetal.
[0021] Preferably, the organic solvent is dimethyl sulfoxide.
[0022] Preferably, the reaction is carried out at a temperature of 55° C. to 65° C., and the reaction time is 2 h to 4 h.
[0023] Preferably, the product is purified by water washing.
[0024] Preferably, the drying comprises the following process: first drying at a temperature of 80°C to 100°C for 10 hours to 15 hours, and then vacuum drying at a temperature of 90°C to 110°C for 20 hours to 30 hours.
[0025] A method for preparing the polyoxometalate-polyvinyl acetal composite film as described above comprises the following steps: dispersing polyvinyl acetal and polyoxometalate molecular clusters in a solvent to prepare a casting liquid, injecting the casting liquid into a mold to form a film, and then drying to obtain a polyoxometalate-polyvinyl acetal composite film.
[0026] Preferably, the dispersion is carried out at a temperature of 85°C to 90°C.
[0027] Preferably, the solvent is a water-propanol mixed solvent.
[0028] Preferably, the volume ratio of water to propanol in the water-propanol mixed solvent is 1:4-6.
[0029] Preferably, the mass fraction of the polyoxometalate molecular clusters in the casting solution is 5% to 80%.
[0030] More preferably, the mass fraction of the polyoxometalate molecular clusters in the casting solution is 5% to 20%.
[0031] Preferably, the drying comprises the following process: first drying at a temperature of 80°C to 100°C for 10 hours to 15 hours, and then vacuum drying at a temperature of 90°C to 110°C for 4 hours to 8 hours.
[0032] A fuel cell comprises the polyoxometalate-polyvinyl acetal composite membrane.
[0033] Preferably, the fuel cell is a hydrogen proton exchange membrane fuel cell.
[0034] The beneficial effects of the present invention are as follows: the polyoxometalate-polyvinyl acetal composite membrane of the present invention has the advantages of excellent solvent resistance, high ion transfer efficiency, good conductivity, high thermal stability, good mechanical properties, low gas permeability, high safety, and easy processing. It is suitable for use as a proton exchange membrane in hydrogen proton exchange membrane fuel cells, and its production cost is low, the manufacturing process is green and streamlined, and it is suitable for large-scale industrial production and application.
[0035] Specifically:
[0036] 1) The polyoxometalate molecular clusters (hydrophilic) and polyvinyl acetal (hydrophobic) in the polyoxometalate-polyvinyl acetal composite membrane of the present invention have good compatibility. The oxygen-containing groups in the polyvinyl acetal can provide binding sites that strongly interact with the polyoxometalate molecular clusters. The polyoxometalate molecular clusters are uniformly dispersed in the polyvinyl acetal through hydrogen bonding to form continuous and efficient ion conduction channels. The composite membrane has a clear microphase structure, which can effectively transfer protons under high humidity conditions. At the same time, the polyvinyl acetal can greatly improve the solvent resistance of the composite membrane, providing a guarantee for the execution of actual production processes such as catalyst spraying, and extending the service life of the composite membrane.
[0037] 2) The polyoxometalate-polyvinyl acetal composite membrane of the present invention contains polyoxometalate molecular clusters and polyvinyl acetal. The polyvinyl acetal imparts good flexibility and solvent resistance to the composite membrane, while the polyoxometalate molecular clusters impart high mechanical strength to the composite membrane. This not only ensures the durability of the composite membrane during processing and use, but also provides a guarantee for the long-term stable operation of the fuel cell.
[0038] 3) The polyoxometalate-polyvinyl acetal composite membrane of the present invention is a uniform solid thin film in a dry state, and has high ion transport efficiency, good electrical conductivity, high thermal stability (it can maintain structural stability at temperatures up to 280°C), good mechanical properties, and low gas permeability (the composite membrane has good gas barrier properties for hydrogen and oxygen, reducing the risk of fuel permeation and improving the safety and operating efficiency of fuel cells). It is highly safe and suitable for use in hydrogen proton exchange membrane fuel cells.
[0039] 4) The properties of the polyoxometalate-polyvinyl acetal composite membrane of the present invention (mainly solvent resistance) can be controlled by the length of the grafted carbon chain of the polyvinyl acetal and the degree of grafting (acetalization degree). Specifically, as the number of carbon atoms in the grafted carbon chain increases, the solvent resistance of the composite membrane is significantly enhanced, the mechanical properties are enhanced, and the proton conductivity is slightly decreased; as the degree of grafting increases, the mechanical properties of the composite membrane are enhanced, and the proton conductivity is slightly decreased.
[0040] 5) The preparation process of the polyoxometalate-polyvinyl acetal composite membrane of the present invention is simple and easy. The polyvinyl acetal is synthesized in a simple one-step reaction. Subsequent molding requires only dissolving the polyoxometalate molecular clusters and polyvinyl acetal in a solvent to form a uniform solution, which is then solution-cast into a membrane. The product process quality is easy to control, and the production cost is significantly lower than that of commercial Nafion proton membranes, which is conducive to industrial large-scale production and application.
[0041] 6) The preparation process of the polyoxometalate-polyvinyl acetal composite film of the present invention is green and environmentally friendly. No fluorine-containing compounds are required in the entire production process, which protects the environment while also reducing production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a graph showing the flexibility test results of the polyoxometalate-polyvinyl acetal composite film of Example 1.
[0043] Figure 2 This is the hydrogen nuclear magnetic resonance spectrum of the polyoxometalate-polyvinyl acetal composite film of Example 1.
[0044] Figure 3 Graph showing the solvent resistance test results of the polyoxometalate-polyvinyl acetal composite films of Example 1, Example 3 and the comparative example.
[0045] Figure 4 The polyoxometalate-polyvinyl acetal composite films of Examples 1 to 4, the polyoxometalate-polyvinyl acetal composite films of the comparative example and SiW 12 SAXS graph.
[0046] Figure 5 The stress-strain curves of the polyoxometalate-polyvinyl acetal composite films of Examples 1 to 4 and the comparative example are shown.
[0047] Figure 6 The polyoxometalate-polyvinyl acetal composite film and SiW of Example 4 12 TGA curve of .
[0048] Figure 7 This is a graph showing the conductivity stability test results of the polyoxometalate-polyvinyl acetal composite film of Example 1.
[0049] Figure 8 This is the polarization curve of the fuel cell assembled with the polyoxometalate-polyvinyl acetal composite membrane of Example 1.
[0050] Figure 9 This is a graph showing the gas barrier performance test results of the polyoxometalate-polyvinyl acetal composite film of Example 1. DETAILED DESCRIPTION
[0051] The present invention will be further explained and illustrated below with reference to specific embodiments.
[0052] Example 1:
[0053] A polyoxometalate-polyvinyl acetal composite film, the preparation method of which is as follows:
[0054] 1) 10 g of PVA124 was added to 400 mL of dimethyl sulfoxide (DMSO), and the mixture was stirred at 90° C. until the PVA124 was fully dissolved. After cooling to 60° C., octanal was added. The molar ratio of the hydroxyl group in PVA124 to the aldehyde group in octanal was 1:0.125. The mixture was stirred at constant temperature for 2 h, filtered, and the solid was washed with water three times, then dried at 90° C. for 12 h, and then vacuum dried at 100° C. for 24 h to obtain polyvinyl octanal acetal (the number of carbon atoms in the carbon side chain was 8, and the degree of acetalization was 25%; denoted as PVO25%).
[0055] 2) 0.5g of polyvinyl octanal and 1g of silicotungstic acid molecular cluster H4[SiW 12 O 40 ] 4- ·mH2O(SiW 12 ) was added to 15 mL of a water-propanol mixed solvent (the volume ratio of water to propanol was 1:5), stirred at 90°C to a uniform transparent solution, cooled to room temperature to obtain a casting solution, injected into a glass mold, and then baked at 50°C for 2 h to form a film. The film was then taken out of the glass mold, dried at 90°C for 12 h, and then vacuum dried at 100°C for 8 h to obtain a polyoxometalate-polyvinyl acetal composite film (PVO25%, SiW 12 The mass ratio is 1:2).
[0056] Example 2:
[0057] A polyoxometalate-polyvinyl acetal composite film, the preparation method of which is as follows:
[0058] 1) 10 g of PVA124 was added to 400 mL of DMSO, and the mixture was stirred at 90° C. until the PVA124 was fully dissolved. After cooling to 60° C., octanal was added, and the molar ratio of the hydroxyl group in PVA124 to the aldehyde group in octanal was 1:0.375. The mixture was stirred at constant temperature for 2 hours, filtered, and the solid was washed with water three times, then dried at 90° C. for 12 hours, and then vacuum dried at 100° C. for 24 hours to obtain polyvinyl octanal acetal (the number of carbon atoms in the carbon side chain was 8, and the degree of acetalization was 75%; denoted as PVO75%).
[0059] 2) 0.5g of polyvinyl octanal and 1g of SiW 12The mixture was added into 15 mL of a water-propanol mixed solvent (the volume ratio of water to propanol was 1:5), stirred at 90 ° C until a uniform transparent solution was obtained, and then cooled to room temperature to obtain a casting solution, which was then injected into a glass mold and dried at 50 ° C for 2 h to form a film. The film was then taken out of the glass mold and dried at 90 ° C for 12 h, and then vacuum dried at 100 ° C for 8 h to obtain a polyoxometalate-polyvinyl acetal composite film (PVO75%, SiW 12 The mass ratio is 1:2).
[0060] Example 3:
[0061] A polyoxometalate-polyvinyl acetal composite film, the preparation method of which is as follows:
[0062] 1) 10 g of PVA124 was added to 400 mL of DMSO, and the mixture was stirred at 90° C. until the PVA124 was fully dissolved. After cooling to 60° C., dodecanal was added, and the molar ratio of the hydroxyl group in PVA124 to the aldehyde group in dodecanal was 1:0.125. The mixture was stirred at constant temperature for 2 hours, filtered, and the solid was washed with water three times, then dried at 90° C. for 12 hours, and then vacuum dried at 100° C. for 24 hours to obtain polyvinyl dodecanal (the number of carbon atoms in the carbon side chain was 12, and the degree of acetalization was 25%; denoted as PVD25%).
[0063] 2) 0.5g of polyvinyl dodecyl acetal and 1g of SiW 12 The mixture was added into 15 mL of a water-propanol mixed solvent (the volume ratio of water to propanol was 1:5), stirred at 90 ° C until a uniform transparent solution was obtained, and then cooled to room temperature to obtain a casting solution. The casting solution was then injected into a glass mold and dried at 50 ° C for 2 h to form a film. The film was then taken out from the glass mold and dried at 90 ° C for 12 h, and then vacuum dried at 100 ° C for 8 h to obtain a polyoxometalate-polyvinyl acetal composite film (PVD25%, SiW 12 The mass ratio is 1:2).
[0064] Example 4:
[0065] A polyoxometalate-polyvinyl acetal composite film, the preparation method of which is as follows:
[0066] 1) 10 g of PVA124 was added to 400 mL of DMSO, and the mixture was stirred at 90° C. until the PVA124 was fully dissolved. After cooling to 60° C., octanal was added, and the molar ratio of the hydroxyl group in PVA124 to the aldehyde group in octanal was 1:0.125. The mixture was stirred at constant temperature for 2 hours, filtered, and the solid was washed with water three times, then dried at 90° C. for 12 hours, and then vacuum dried at 100° C. for 24 hours to obtain polyvinyl octanal acetal (the number of carbon atoms in the carbon side chain was 8, and the degree of acetalization was 25%; denoted as PVO25%).
[0067] 2) 0.5g of polyvinyl octanal and 2g of SiW 12 The mixture was added into 15 mL of a water-propanol mixed solvent (the volume ratio of water to propanol was 1:5), stirred at 90 ° C until a uniform transparent solution was obtained, and then cooled to room temperature to obtain a casting solution. The casting solution was then injected into a glass mold and dried at 50 ° C for 2 h to form a film. The film was then taken out from the glass mold and dried at 90 ° C for 12 h, and then vacuum dried at 100 ° C for 8 h to obtain a polyoxometalate-polyvinyl acetal composite film (PVO25%, SiW 12 The mass ratio is 1:4).
[0068] Comparative Example:
[0069] A polyoxometalate-polyvinyl acetal composite film, the preparation method of which is as follows:
[0070] 1) 10 g of PVA124 was added to 400 mL of DMSO, and the mixture was stirred at 90° C. until the PVA124 was fully dissolved. After cooling to 60° C., butyraldehyde was added. The molar ratio of the hydroxyl group in PVA124 to the aldehyde group in butyraldehyde was 1:0.125. The mixture was stirred at constant temperature for 2 hours, filtered, and the solid was washed with water three times. The solid was then dried at 90° C. for 12 hours and then vacuum dried at 100° C. for 24 hours to obtain polyvinyl butyral (the carbon number of the carbon side chain was 4 and the degree of acetalization was 25%; denoted as PVB25%).
[0071] 2) 0.5g of polyvinyl butyral and 1g of SiW 12 The mixture was added into 15 mL of a water-propanol mixed solvent (the volume ratio of water to propanol was 1:5), stirred at 90 ° C until a uniform transparent solution was obtained, and then cooled to room temperature to obtain a casting solution. The casting solution was then injected into a glass mold and dried at 50 ° C for 2 h to form a film. The film was then taken out from the glass mold and dried at 90 ° C for 12 h, and then vacuum dried at 100 ° C for 8 h to obtain a polyoxometalate-polyvinyl acetal composite film (PVB25%, SiW 12 The mass ratio is 1:2).
[0072] Performance testing:
[0073] 1) The flexibility test results of the polyoxometalate-polyvinyl acetal composite film of Example 1 are as follows: Figure 1 shown.
[0074] Depend on Figure 1 It can be seen that the polyoxometalate-polyvinyl acetal composite film has uniform texture, is bendable, has good mechanical properties, and can be used as a diaphragm material in fuel cells.
[0075] In addition, the same test shows that the polyoxometalate-polyvinyl acetals of Examples 2 to 4 have uniform texture, are bendable, and have good mechanical properties, and can be used as diaphragm materials in fuel cells.
[0076] 2) The nuclear magnetic resonance hydrogen spectrum of the polyoxometalate-polyvinyl acetal composite film of Example 1 is as follows Figure 2 shown.
[0077] Depend on Figure 2 It can be seen that there are no other impurities except a small amount of residual solvent, and the acetal degree is calculated to be about 25% based on the peak area ratio, which is in line with expectations, indicating that a polyoxometalate-polyvinyl acetal composite film with the expected composition is indeed obtained.
[0078] 3) The polyoxometalate-polyvinyl acetal composite films of Example 1, Example 3 and the comparative example were immersed in an ethanol-water mixed solvent (the volume ratio of ethanol to water was 1:1) to simulate the actual catalyst spraying process. The immersion time was 1 hour, and then the solvent absorption mass ratio and the swelling volume ratio were calculated. The solvent resistance test results were as follows: Figure 3 shown.
[0079] Note:
[0080] The calculation formula of solvent absorption mass ratio (WU) is as follows: WU (%) = (W wet -W dry ) / W dry ×100%, where W wet Represents the weight of the composite membrane after immersion, W dry Represents the weight of the composite film after drying (drying to avoid SiW 12 A small amount of leaching occurs during the soaking process, affecting the absorption quality).
[0081] The calculation formula of swelling volume ratio (SR) is as follows: SR (%) = (X wet -X dry ) / X dry ×100%, where X wet represents the side length of the composite membrane after immersion, X dry Represents the side length of the composite membrane before immersion.
[0082] Depend on Figure 3 It can be seen that the polyoxometalate-polyvinyl acetal composite film of the comparative example dissolves in the solvent and has poor solvent resistance; the polyoxometalate-polyvinyl acetal composite films of Examples 1 and 3 do not dissolve, and the swelling volume ratio is less than 20%, and have excellent solvent resistance.
[0083] In addition, the same test shows that the polyoxometalate-polyvinyl acetal composite films of Examples 2 and 4 have excellent solvent resistance.
[0084] 4) The polyoxometalate-polyvinyl acetal composite films of Examples 1 to 4, the polyoxometalate-polyvinyl acetal composite films of the comparative example, and the silicotungstic acid molecular cluster H4[SiW 12 O 40 ] 4- ·mH2O(SiW 12 ) small angle X-ray scattering (SAXS) pattern as shown in Figure 4 shown.
[0085] Depend on Figure 4 It can be seen that the silicotungstic acid molecular clusters in the polyoxometalate-polyvinyl acetal composite films of Examples 1 to 4 and the comparative example are in a uniformly dispersed state.
[0086] 5) The polyoxometalate-polyvinyl acetal composite films of Examples 1 to 4 and the comparative example were subjected to tensile tests, and the obtained stress-strain curves were as follows: Figure 5 The Young's modulus and elongation at break test results (measured by tensile testing at a rate of 10 mm / min) are shown in the following table:
[0087] Table 1 Test results of Young's modulus and elongation at break of polyoxometalate-polyvinyl acetal composite films
[0088] Test items Young's modulus (MPa) Elongation at break (%) Example 1 105 15 Example 2 362 6 Example 3 168 5 Example 4 57 11 Comparative Example 35 55
[0089] Depend on Figure 5 From Table 1, we can see that:
[0090] a) The polyoxometalate-polyvinyl acetal composite films of Examples 1 to 4 have a relatively high Young's modulus, indicating that the polyoxometalate-polyvinyl acetal composite films of the present invention have a high mechanical strength;
[0091] b) As the number of carbon atoms in the side chain of polyvinyl acetal increases (Comparative Example → Example 1 → Example 3), the elongation at break of the polyoxometalate-polyvinyl acetal composite film decreases and the Young's modulus increases;
[0092] c) As the degree of acetalization of polyvinyl acetal increases (Example 1 → Example 2), the elongation at break of the polyoxometalate-polyvinyl acetal composite film decreases and the Young's modulus increases;
[0093] d) As the mass ratio of the polyoxometalate molecular clusters to the polyvinyl acetal increases (Example 1→Example 4), the elongation at break and the Young's modulus of the polyoxometalate-polyvinyl acetal composite film decrease.
[0094] 6) The polyoxometalate-polyvinyl acetal composite film and the silicotungstic acid molecular cluster H4[SiW 12 O 40 ] 4- ·mH2O(SiW 12 )’s thermogravimetric (TGA) curve is as follows Figure 6 shown.
[0095] Depend on Figure 6 It can be seen that the extrapolated decomposition starting temperatures of the polyoxometalate-polyvinyl acetal composite film and silicotungstic acid molecular clusters of Example 4 are both above 280°C, and both have relatively high decomposition temperatures (>280°C), indicating that the polyoxometalate-polyvinyl acetal composite film has excellent thermal stability.
[0096] In addition, the same test shows that the polyoxometalate-polyvinyl acetal composite films of Examples 1 to 3 have excellent thermal stability.
[0097] 7) The conductivity stability test results of the polyoxometalate-polyvinyl acetal composite film of Example 1 (simulating a real working environment, temperature of 60°C, relative humidity of 100%) are as follows: Figure 7 As shown, the room temperature conductivity test results of the polyoxometalate-polyvinyl acetal composite membranes of Examples 1 to 4 and the comparative example are shown in the following table (an AC potential wave with a small amplitude and different frequencies is applied to the electrochemical system, and the ratio of the AC potential to the current signal is measured as a function of the sine wave frequency ω, or the phase angle Φ of the impedance is measured as a function of ω, and the ionic conductivity σ of the composite membrane sample is calculated; the ionic conductivity calculation formula is: σ = d / AR, where d is the thickness of the polyoxometalate-polyvinyl acetal composite membrane in cm, and A is the electrode area in cm 2 , R is the resistance obtained by AC impedance method, unit is Ω):
[0098] Table 2 Test results of room temperature electrical conductivity of polyoxometalate-polyvinyl acetal composite membrane
[0099] Test items Conductivity at room temperature (mS / cm) Example 1 4.5 Example 2 0.3 Example 3 2.2 Example 4 7.8 Comparative Example 8.9
[0100] Depend on Figure 7As shown in Table 2, the polyoxometalate-polyvinyl acetal composite membranes of Examples 1 to 4 have high ionic conductivity, can effectively realize proton transfer, and have high electrochemical stability in a real working environment with high humidity.
[0101] 8) The polyoxometalate-polyvinyl acetal composite membrane of Example 1 and two gas diffusion electrodes were assembled into a sandwich membrane electrode assembly by hot pressing, and then installed in a fuel cell experimental device for testing (simulating a real working environment, temperature of 70°C, relative humidity of 100%). The polarization curves obtained are shown in FIG. Figure 8 shown.
[0102] Depend on Figure 8 It can be seen that the power density of the fuel cell assembled with the polyoxometalate-polyvinyl acetal composite membrane of Example 1 is 608 mW / cm at a temperature of 70°C and a relative humidity of 100%. 2 (The open circuit potential is 0.92 V), indicating that the polyoxometalate-polyvinyl acetal composite membrane is suitable for use in fuel cells and is suitable for use in high humidity environments.
[0103] In addition, the same test shows that the polyoxometalate-polyvinyl acetal composite membranes of Examples 2 to 4 are suitable for use in fuel cells and are suitable for use in high humidity environments.
[0104] 9) The polyoxometalate-polyvinyl acetal composite film of Example 1 is placed between the two chambers of the test chamber, sealed, and the lower chamber is evacuated, while the upper chamber is maintained with a certain pressure of test gas. As gas molecules pass through the polyoxometalate-polyvinyl acetal composite film, the pressure in the lower chamber gradually increases. This change is monitored by a high-precision pressure sensor, and the gas permeation per unit area per unit time is calculated. The gas barrier test results are as follows: Figure 9 shown.
[0105] Depend on Figure 9 It can be seen that the polyoxometalate-polyvinyl acetal composite film of Example 1 has extremely strong gas barrier properties, and the gas barrier coefficients of hydrogen and oxygen are small (<10 -12 cm 2 ·s·Pa), which can effectively prevent the fuel crossover phenomenon in fuel cell equipment and ensure the stable application of polyoxometalate-polyvinyl acetal composite membrane in fuel cells.
[0106] In addition, the same test shows that the polyoxometalate-polyvinyl acetal composite films of Examples 2 to 4 have extremely strong gas barrier properties.
[0107] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be considered as equivalent replacement methods and are included in the scope of protection of the present invention.
Claims
1. A polyoxometalate-polyvinyl acetal composite film, characterized in that: The composition includes polyvinyl acetal and polyoxometalate molecular clusters; the polyvinyl acetal is prepared by reacting polyvinyl alcohol and straight-chain aldehyde compounds.
2. The polyoxometalate-polyvinyl acetal composite film according to claim 1, characterized in that: The mass ratio of the polyvinyl acetal to the polyoxometalate molecular cluster is 1:0.5-8.
3. The polyoxometalate-polyvinyl acetal composite film according to claim 1 or 2, characterized in that: The polyoxometalate molecular cluster is a Keggin-type polyoxometalate molecular cluster.
4. The polyoxometalate-polyvinyl acetal composite film according to claim 3, characterized in that: The general structural formula of the Keggin-type polyoxometalate molecular cluster is as follows: n [XM 12 O 40 ] n- ·mH2O, wherein X represents the central atom, X is selected from at least one of P, Si, Co, and Al, Y represents the counter ion, Y is selected from at least one of H, Li, Na, and K, M represents the coordinating atom, M is selected from at least one of Nb, W, and Mo, m represents the number of crystal waters, the number of m depends on the self-bound water and the specific environmental humidity, m is an integer from 0 to 40, and n represents the number of charges carried by the polyanion / the number of counter ions, and n is 3, 4, or 6.
5. The polyoxometalate-polyvinyl acetal composite film according to claim 1 or 2, characterized in that: The molar ratio of the hydroxyl group in the polyvinyl alcohol to the aldehyde group in the straight-chain aldehyde compound is 1:0.125-0.
375.
6. The polyoxometalate-polyvinyl acetal composite film according to claim 1 or 2, characterized in that: The number average molecular weight of the polyvinyl alcohol is 30,000 g / mol to 300,000 g / mol.
7. The polyoxometalate-polyvinyl acetal composite film according to claim 1 or 2, characterized in that: The straight-chain aldehyde compound is C8~C 12 of straight-chain aldehyde compounds.
8. The polyoxometalate-polyvinyl acetal composite film according to claim 1 or 2, characterized in that: The polyvinyl acetal is prepared by a preparation method comprising the following steps: dispersing polyvinyl alcohol and a linear aldehyde compound in an organic solvent to react, and then purifying and drying the product to obtain the polyvinyl acetal.
9. A method for preparing a polyoxometalate-polyvinyl acetal composite film according to any one of claims 1 to 8, characterized in that: The following steps are involved: Polyvinyl acetal and polyoxometalate molecular clusters are dispersed in a solvent to prepare a casting solution, which is then injected into a mold to form a film, and then dried to obtain a polyoxometalate-polyvinyl acetal composite film.
10. A fuel cell, characterized in that: A polyoxometalate-polyvinyl acetal composite film comprising the polyoxometalate-polyvinyl acetal composite film according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method of phosphotungstic acid-polyvinyl formal composite proton exchange membrane
CN103627012A
Fluorine-free proton exchange membrane as well as preparation method and application thereof
CN116960418A
Blend-cross-linked polymer electrolyte membrane
JP2006156055A